The Role of PAI Teachers in Overcoming the Ability to Read the Qur'an - Selian, Bagas Nirwana; Silahuddin, Silahuddin (AR-RASYID : Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in improving the ability to read the Qur'an at MA Darut Tahfidz Ajun, where PAI teachers function as educators as well as role models for students in the context of education that emphasizes the importance of mastering the Qur'an. The research method used is descriptive qualitative, with data collection through interviews, observation, and documentation. The results showed that PAI teachers implemented various strategies, such as self-reward, personal approach, implementation of tadarus before learning, and periodic evaluation to help students in reading the Qur'an. In addition, support from a conducive learning environment and parental involvement also contributed significantly to the development of students' abilities. This study recommends the need for continuous training for PAI teachers as well as the development of innovative teaching methods to further improve the quality of Qur'anic learning in these educational institutions. With various efforts made by teachers, students' Qur'an reading ability can be improved significantly.